2019
DOI: 10.1038/s41598-019-51960-w
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone causes pleiotropic effects on cleanerfish behaviour

Abstract: Mathematical modelling regarding evolutionary theory typically assumes that optimal strategies are not constrained through mechanistic processes. In contrast, recent studies on brain anatomy and neurobiology suggest that flexibility in social behaviour is rather constrained by the physiological state of the social decision-making network. Changing its state may yield selective advantages in some social contexts but neutral or even detrimental effects in others. Here we provide field evidence for such physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 67 publications
(113 reference statements)
2
3
0
Order By: Relevance
“…They forage by removing ectoparasites from other fish, socalled clients [37], and are organized into dominance hierarchies of females and a top-ranking male that has undergone sex reversal [38]. The study [36] found that testosterone-injected females increased their aggression towards subordinate females and spent less time interacting with clients, which supports our model assumptions. In general, cleaner fish, could be an example where female competition is relatively close to global, because they forage on non-monopolizable resources (clients) and reproduce through pelagic eggs.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…They forage by removing ectoparasites from other fish, socalled clients [37], and are organized into dominance hierarchies of females and a top-ranking male that has undergone sex reversal [38]. The study [36] found that testosterone-injected females increased their aggression towards subordinate females and spent less time interacting with clients, which supports our model assumptions. In general, cleaner fish, could be an example where female competition is relatively close to global, because they forage on non-monopolizable resources (clients) and reproduce through pelagic eggs.…”
Section: Discussionsupporting
confidence: 73%
“…Hormonal manipulation is another way to examine such a trade-off, and this has been performed on cleaner fish in the wild [36]. Cleaner fish ( Labroides dimidiatus ) live on coral reefs.…”
Section: Discussionmentioning
confidence: 99%
“…They forage by removing ectoparasites from other fish, so-called clients [33], and are organised into dominance hierarchies of females and a top-ranking male that has undergone sex reversal [34]. The study [32] found that testosterone-injected females increased their aggression towards subordinate females and spent less time interacting with clients, which supports our model assumptions. In general, cleaner fish, could be an example where female competition is relatively close to global, because they forage on non-monopolisable resources (clients) and reproduce through pelagic eggs.…”
Section: Discussionsupporting
confidence: 72%
“…Hormonal manipulation is another way to examine such a trade-off, and this has been performed on cleaner fish in the wild [32]. Cleaner fish ( Labroides dimidiatus ) live on coral reefs.…”
Section: Discussionmentioning
confidence: 99%
“…In general, increased parasite load should make clients more tolerant, but the exact function may vary between species for various reasons (e.g. differences in manoeuvrability; Roche et al 2021, or punishment being co-opted by intraspecific aggressiveness; Soares et al 2019). As a consequence, the model predicts that satiated cleaner fish may behave more cooperatively towards more 'cautious' client species and more exploitative towards more 'easygoing' client species (Triki et al 2022).…”
Section: Part 4: Game Theoretic Modelmentioning
confidence: 99%